1982
DOI: 10.1271/bbb1961.46.2003
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin production by roseoflavin-resistant strains of some bacteria.

Abstract: Riboflavin(RF)-productivity of reseoflavin(RoF)-resistant strains of Staphylococcus aureus, Bacillus pumilusand Bacillus subtilis was studied. Twoof three types of resistant strains of S. aureus were shownto producemore RFthan the parent strains. Resistant strains of B. pumilus were also RF-producing, and one type (fp) of the resistant strains from B. subtilis HWproduced a large amount of RFin the culture medium.The hereditary stability of RF-producing properties of thefp type was also shown. RoF,1}i.e., 8-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Bacillus subtilis wild-type (strain 168) is sensitive to the antibiotic roseoflavin, however, roseoflavin resistant strains easily can be selected on solid growth media [37]. Some of these roseoflavin resistant B. subtilis strains were found to overproduce riboflavin which is an antagonist to roseoflavin [37].…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus subtilis wild-type (strain 168) is sensitive to the antibiotic roseoflavin, however, roseoflavin resistant strains easily can be selected on solid growth media [37]. Some of these roseoflavin resistant B. subtilis strains were found to overproduce riboflavin which is an antagonist to roseoflavin [37].…”
Section: Resultsmentioning
confidence: 99%
“…Roseoflavin, a toxic riboflavin analog, is often used as an efficient chemical mutagen to induce bacterial spontaneous mutation that is accompanied with increased riboflavin production [33]. In this study, roseoflavin was used to induce the spontaneous mutation of the RYG-YYG-9049 strain, and 10 mutant strains were then randomly selected in CDM agar plates.…”
Section: Riboflavin Production Was Increased In Roseoflavin-induced Mmentioning
confidence: 99%
“…Recently, it has been confirmed that several previously identified antibacterial compounds might function by targeting riboswitches, including pyrithiamine [98,99], L-aminoethylcysteine (AEC) [100], DL-4-oxalysine [101], and roseoflavin ( Figure 10) [102,103]. Pyrithiamine is an analog of thiamine.…”
Section: Riboswitchesmentioning
confidence: 95%